Explicating Cultural Concepts - Niebrzegowska-Bartmińska, Stanisława (Vilnius University Open Series, 2020)
Ethnolinguistics deals with collective identities and reality-interpreting narratives. Collective identity (beliefs, values, and their symbolisations shared by a community) is defined as a mental construct, access to which can be obtained through complementary and linguistically “externalised” images. Inquiry into identity is the most effective when it is concerned with language, both in the narrower sense of linguistic structure and textual narratives, and in the broader semiotic sense. Whichever option is selected, the important issues to be addressed include the linguistic phenomena that make up identity, the methodology of identity research, as well as the data on the basis of which collective identity can be reconstructed. In this study, attention is paid to narrative linguistic phenomena: language is viewed as a most human phenomenon and a significant social fact that contributes to the construction of collective identity. The notion of “reality-interpreting narratives” pertains to subjectivised stories of the world, more or less stable judgements, stories that interpret reality and assume the shape of cognitive definitions. In the course of thirty years of work on and with the cognitive definition, two types of ethnolinguistic description have emerged: holistic (integrated) and separated (isolated). The former is preferred in the Dictionary of Folk Stereotypes and Symbols, the latter in the Axiological Lexicon of Slavs and Their Neighbours. Both types of description reveal the functioning of images (sterotypes/concepts) in a network of relationships that allows one to capture the system of values that underlies the languages and cultures being studied. These relationships are here illustrated with the Polish images of róża ‘rose’ and wolność ‘freedom’.